UNION COMMITMENT AND ACADEMIC STAFF PERFORMANCE OF PUBLIC HIGHER INSTITUTIONS IN NIGERIA (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
The study investigated the relationship between union commitment and academic staff performance in Nigerian universities. The study adopted survey design. The population of the study was 1306 academic staff of public higher institutions in Rivers State, Nigeria with 297 determined sample size. Cluster sampling method was used because of the unavailability of comprehensive academic staff list. Pearson Product Moment Correlation and Partial Correlation were the statistical tools used in testing the nine hypotheses. The findings revealed that there exist relationship between union commitment and academic staff performance and that with favourable industrial relation climate, union commitment will positively aid the academic staff performance in Nigerian public higher institutions. It was, therefore, recommended that management should help promote cordial/conducive industrial relation climate with routine meetings and/or discussion forum between the trade union and the management so as to improve performance of academic staff of higher institutions of learning